Parkinson’s Disease: Physiopathologic and Therapeutic Aspects - Ferreira, Flavio Dias (2010)
The Parkinson’s Disease (PD) is one of the most frequent degenerative affections of the central nervous system, of progressive character, that attacks base nuclei. Clinically, it is characterized by rest tremor, muscular rigidity and bradicinesia. With the progression of the disease, the patient has gradual limitation on that independence with damages for his autonomy. The physical-mental, emotional, social and economical issues associated to the signs and symptoms and to the secondary complications of PD interfere in the individual's incapacity level and can negatively influence his quality of life. The levodopa is the metabolic precursor of the dopamine and separately the most effective drug for the treatment of PD. Practically, the use of this drug is associated with Carbidopa or Benserazide, because while administered separately it is largely decarboxilated. Its use relieves some of the symptoms related to the motor part of PD. The bibliographical research was carried out on index sites and some books regarding the subject. This review makes it clearer that the evolution of the disease is variable, because the patients can be little disabled and spend many years with the same symptoms while the progression in other patients is faster. What we should keep clear is that, with the available therapeutic resources, in most of the cases, it is possible to maintain the patient in clinical conditions that allow him, for long periods, to live a normal life, or close to this, although a radical, definitive cure is still not possible.